Hubungan Inisiasi Menyusui Dini dengan Kestabilan Suhu Tubuh pada Bayi Baru Lahir di RS Muhammadiyah Gresik Kabupaten Gresik: Relationship between Early Initiation of Breastfeeding and Stability of Body Temperature in Newborns at Muhammadiyah Hospital Gresik, Gresik Regency - Ernawati, Ernawati; Nuraini, Nanik (Jurnal Kebidanan Midwiferia, 2019)
The problem discussed in this scientific paper is the relationship between the initiation of Early Breastfeeding and the stability of the newborn's body temperature, the aim is to find out the relationship of the initiation of Early Breastfeeding with the stability of the body temperature of the newborn. The purpose of this study is the relationship between Early Breastfeeding Initiation and Body Temperature Stability in Newborns at Muhammadiyah Hospital Gresik, Gresik Regency. In this study using a case control approach. The population in this study were 39 newborns in Muhammadiyah Hospital Gresik, Gresik Regency. The study sample was 20 newborns at Muhammadiyah Hospital Gresik taken from the population by determining the sample size using the Slovin formula. The design of this study used a case-control design. Cases were taken from infants that received IMD while controls were newborns who had normal body temperature. Techniques data collection through interviews and observations to obtain primary data, while secondary data are obtained by tracking the patient's medical record documents. Data processing techniques follow the steps : editing, coding, data entry, tabulation, and scoring. While the data analysis used the Chi Square test. The results of the bivariate analysis showed that the value of X2hit (10,588)> X2 table (3.8415) or p-value (0.009) <alpha (0.05). Based on these results the null hypothesis (Ho) is rejected. The alternative hypothesis (Ha) is accepted, meaning that there is a relationship between the initiation of early breastfeeding and the stability of body temperature in newborns at Muhammadiyah Hospital Gresik.